PENGARUH SUPLEMENTASI MULTIVITAMIN MINERAL TERHADAP STATUS GIZI DAN KESEHATAN - Rimbawan .; Dadang Sukandar; Febrina Sulistiawati; Fitrah Ernawati (GIZI INDONESIA, 2009)
THE EFFECT OF MULTIVITAMIN MINERAL SUPPLEMENTATION ON NUTRITIONAL STATUS AND HEALTHUse of multivitamin mineral (MVM) supplement has grown rapidly over the past several decades.According to several studies, supplement users tend to have higher micronutrient intakes from theirdiet than nonusers. Consequently, they have an increased intake but are also more likely to exceedthe upper level. The study was aimed to analyze the effect of MVM supplementation on renal functionthrough the double blind randomized controlled trial. Subjects were 93 of the female workers in PTRicky Putra Globalindo Tbk, Citeureup, Bogor who were randomly allocated to three treatments. Thefirst received only placebo (without vitamin C and MVM); the second received 1000 mg vitamin C; andthe third received MVM supplement that contains 1000 mg vitamin C, 45 mg vitamin E, 700 µg vitaminA, 6,5 mg vitamin B6, 400 µg folic acid, 9,6 µg vitamin B12, 10 µg vitamin D, 10 mg Zn, 110 µg Se, 0,9mg Cu, and 5 mg Fe. The supplements were distributed and consumed daily during 10 weeks. Themean change before and after study were tested with t paired test. The results showed the BMI,systolic and diastolic blood pressure, urea and creatinine blood serum were not significantly differentbefore and after study (p0,05). The distribution of female workers based on BMI showed that morethan half of them have normal nutritional status (BMI 18,5-24,9 kg/m2). The distribution based onsystolic and diastolic blood pressure showed that most of them were not hypertension (systolic 140mmHg, diastolic 90 mmHg); and the distribution based on urea and creatinine showed that most ofthem have normal status (urea 8,0-25,0 mg/dl; creatinine 0,6-1,5 mg/dl).Keywords: food supplement, BMI, blood pressure, urea, creatinine.